Defect Characterization in High‐Electron‐Mobility Transistors with Regrown p‐GaN Gate by Low‐Frequency Noise and Deep‐Level Transient Spectroscopy. Issue 23 (29th July 2021) - Hsu, Po-Chun; Simoen, Eddy; Liang, Hu; De Jaeger, Brice; Bakeroot, Benoit; Wellekens, Dirk; Decoutere, Stefaan
Abstract : To investigate the defects from the gate regrowth process, samples with and without regrowth p‐GaN process are fabricated by metalorganic chemical vapor deposition (MOCVD). The DC characteristics indicate larger gate leakage ( I gs ) between the GaN channel and the p‐GaN gate in the regrowth sample than in the nonregrowth counterpart. In addition, significant Si/O impurities are introduced by the regrowth process at the interface between channel and regrown AlGaN barrier. The low‐frequency noise (LFN) measurement and deep‐level transient spectroscopy (DLTS) are further carried out to investigate the defectivity at the AlGaN barrier and channel interface, giving a 2–3 times higher border trap density in the AlGaN barrier (depth ≈5 nm from the channel interface) and a 10 times increase in interface trap density at the channel interface, corresponding with a band of shallow levels E3 =  E c –0.02–0.15 eV. Three additional bulk traps E2/E5 ( E c –0.8 eV, σ n = 5 × 10 − 15   cm 2 / E c –0.17 eV, σ n = 5 × 10 − 22   cm 2 ) and E4 ( E c –0.23 eV, σ n = 5 × 10 − 19   cm 2 ) are also found in the regrowth and nonregrowth samples, respectively. Their possible spatial locations and origins are discussed. Abstract : The electrical properties of the defects originated from the p‐GaN gate regrowth process are studied by using deep‐level transient spectroscopy (DLTS) and low‐frequency noise (LFN) techniques. Several traps and high interface states corresponding to high gate leakage are found at channel regions. Their possible origins are discussed.